Tanzania - Can a Simple Teacher Incentive System Improve Learning? - World Bank (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund at the World Bank co-funded an evaluation that compared the effectiveness of two different teacher performance pay sys - tems in early primary schools in Tanzania. These performance pay systems are part of KiuFunza , an experimental teacher pay program introduced by Twaweza East-Africa, a civil society orga - nization, in collaboration with the Abdul Latif Jameel Poverty Action Lab (J-PAL), Innovations for Poverty Action (IPA) and Economic Development Initiatives (EDI).